2015
DOI: 10.1111/vop.12280
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of accelerated corneal collagen cross‐linking for the treatment of bullous keratopathy in eight dogs (10 eyes)

Abstract: CXL is a useful treatment option for BK in dogs, despite the short-lasting effects on corneal thickness. Patient comfort improved rapidly after a single procedure, although CXL did not achieve resolution of corneal edema. Treatment protocols may be refined to produce more durable effects on corneal edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 29 publications
2
39
0
Order By: Relevance
“…Our results demonstrated that CXL combined with SK reduced corneal thickness but caused only a transient effect on corneal clarity. CT was significantly reduced immediately after the treatment, but progressively increased during the follow‐up period as observed in previous studies evaluating the effect of CXL on bullous keratopathy in human and veterinary patients …”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Our results demonstrated that CXL combined with SK reduced corneal thickness but caused only a transient effect on corneal clarity. CT was significantly reduced immediately after the treatment, but progressively increased during the follow‐up period as observed in previous studies evaluating the effect of CXL on bullous keratopathy in human and veterinary patients …”
Section: Discussionsupporting
confidence: 76%
“…Patients were comfortable after the treatment but the initially decreased corneal thickness gradually increased to preoperative values during the first 4 months after CXL . More recently, Famose observed a long‐lasting decrease in corneal thickness but also reported a return to preoperative values 6 months after accelerated CXL in ten eyes of ten dogs …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bullous keratopathy and associated corneal ulceration can occur in advanced stages of PCED if the edema coalesces into sub‐epithelial bullae that then rupture. This superficial corneal ulceration can cause marked pain that can be protracted because the ulcers are often non‐healing or take extended periods of time to heal . Several different surgical techniques to treat PCED‐associated corneal ulceration, with their relative advantages and disadvantages, have been described in the veterinary literature .…”
Section: Introductionmentioning
confidence: 99%